Occurrence and risk assessment of antibiotic residues in Mediterranean olive grove soils with different management: an EU-wide pilot study - Andrés J. Rascón; Alfonso Fernández-García; David Moreno-Gónzalez; Bienvenida Gilbert-López; Antonio J. Manzaneda; Juan F. García-Reyes (Environmental Research, 2026)

Sediment-Macrophyte Interactions in Heavy Metal Contaminated Lakes: Insights into Bioaccumulation and Phytoremediation Potential - Gilbert Ndatimana; Unique N. Keke; Diana Nantege; Victoria I. Chukwuemeka; Simon Action; Attobla F. Assie; Auta Y. Iliya; Suleiman M. Abdullahi; Adesola V. Ayanwale; Francis O. Arimoro (Water, Air, & Soil Pollution, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Assessment of exposure to pesticides, anticoagulant rodenticides, and PFASs in the blood of top-predator birds by LC-MS/MS analysis - Alfonso Fernández-García; Francisco M. Camacho; David Moreno-González; Ana B. Martínez-Piernas; Bienvenida Gilbert-López; Juan F. García-Reyes (Environmental Research, 2026)

Rugged LC-MS/MS method for the large-scale monitoring of glyphosate and other highly polar pesticides in soils across European Union olive orchards - Alfonso Fernández-García; David Moreno-González; Andrés J. Rascón; Ana B. Martínez-Piernas; Bienvenida Gilbert-López; Antonio J. Manzaneda; Juan F. García-Reyes (Environmental Pollution, 2025)

Disparities in human papillomavirus vaccination uptake across the intersection of disability and sexual orientation - Amarachukwu F. Orji; Gilbert Gimm; Tarang Parekh; Rodman Turpin; Carolyn Drews-Botsch (Cancer Causes & Control, 2025)
Purpose Although human papillomavirus (HPV) vaccination provides effective primary prevention against cervical cancer, HPV vaccination rates remain low in the U.S. It is unknown whether women with disabilities and/or LGB + women are likely to experience disparities in HPV vaccination uptake. Methods We used data from the 2014–2022 Behavioral Risk Factor Surveillance System ( N = 40,401) to estimate HPV vaccination rates among women aged 18–44 years. Adjusted prevalence ratios (aPRs) were estimated using modified Poisson regression models for four subgroups defined by disability status and LGB + status. Analyses were further stratified by age (18–26 years; 27–44 years). Results Overall, only 19% of eligible women had received at least one dose of the HPV vaccine, and 12% had completed the full series. Younger women were more likely than older women to have been vaccinated. Compared with heterosexual women without disabilities, heterosexual women with disabilities, had lower vaccination uptake (heterosexual with disabilities: aPR = 0.95; 95% CI 0.93–0.97; LGB + with disabilities: aPR = 0.97; 95% CI 0.96–0.98), and were 12% less likely to complete the series (heterosexual with disabilities: aPR = 0.88; 95% CI 0.83–0.93). Conclusion HPV vaccination rates remain low, representing missed opportunities for primary prevention. Women with disabilities had lower vaccination rates than women without disabilities and were less likely to complete the vaccine series. These findings, combined with age-stratified results, highlight the need for stronger catch-up campaigns and targeted efforts to address structural barriers related to disability, ultimately improving HPV vaccination coverage and reducing the burden of cervical cancer.

Coral reef boulders as recorders of cyclone activity over the last 3500 years (Fakarava Atoll, Tuamotu, French Polynesia) - Lucien F. Montaggioni; Bernard Salvat; Éric Brunaud; Edwige Pons-Branchu; Gilbert Poli; Bertrand Martin-Garin (Marine Geology, 2025)

Determination of free and derivative terpenoids and sterols in spent coffee grounds by two-dimensional liquid chromatography - supercritical fluid chromatography coupled to high-resolution mass spectrometry - Irene Caño-Carrillo; Magali Batteau; Lauriane Bruna; Bienvenida Gilbert-López; Juan F. García-Reyes; Gregory Chatel; Karine Faure (Food Chemistry, 2025)

Intracerebroventricular injection of taurine affords thermotolerance and regulates mitochondrial thermogenic gene expression in pectoralis muscle in neonatal chicks exposed to high ambient temperature - Mohamed Z. Elhussiny; Haruka Nishimura; Shogo Haraguchi; Elizabeth R. Gilbert; Mark A. Cline; John F. Cockrem; Eiki Takahashi; Yoshimitsu Ouchi; Takashi Bungo; Vishwajit S. Chowdhury (Journal of Thermal Biology, 2025)

Mid- to Late-Holocene branched GDGT-based air temperatures from a crater lake in Cameroon (Central Africa) - Guillemette Ménot; Salomé Ansanay-Alex; Valérie F. Schwab; Gilbert Todou; Olivier Séné; Jean-Michel Onana; Gerd Gleixner; Dirk Sachse; Yannick Garcin (Organic Geochemistry, 2025)

Historical genomic variation of Eurasian otters (Lutra lutra) in Britain, from hunting trophies - Sarah J. du Plessis; Nuno F. Martins; Xin Sun; Sarah S. T. Mak; David W. G. Stanton; Klaus-Peter Koepfli; Elizabeth A. Chadwick; M. P. Thomas Gilbert; Frank Hailer (Conservation Genetics Resources, 2025)
Genomic data from historical specimens can provide insights into populations and processes no longer evident from modern samples. Identifying viable sources of historical DNA is key to this. Here we aimed to explore the viability of trophy hunting paws as sources of historical DNA, and to use this data for preliminary analyses to evaluate changes in population structuring over time. We aimed to search for the presence of genomic signals of the putative recent introduction of Eurasian otters ( Lutra lutra ) from Asia to the UK previously identified using modern data, by analysis of two trophy paws from 1929 to 1952. Substantial proportions of endogenous DNA (77–85%) were identified in both samples for which genomic DNA extraction and sequencing was attempted, illustrating the potential of such specimens for historical DNA research. Autosomal variation suggests that the historical specimens cluster closest to modern specimens from Wales, and not with the variation identified in the East of England, putatively associated with the recent introduction of Eurasian otters from Asia. Similarly, the divergent mitochondrial lineage found in modern otters from the East of England and Asia, was not found in the historical British specimens. Although limited inferences can be made from a sample size of two, this preliminary dataset indicates the huge potential of historical trophy paw samples to assess past population genetic dynamics, calling for further research in this area.

Dephasing of islet building between leeward and windward reef-rim sides, Bora Bora Island, Society Archipelago, central South Pacific - Lucien F. Montaggioni; Bernard Salvat; Edwige Pons-Branchu; Bertrand Martin-Garin; Gilbert Poli; Marie-Thérèse Vénec-Peyré; David Lecchini; Gaston Tong Sang (Quaternary International, 2025)

Mineralogy, mineral chemistry, and genesis of Cu-Ni-As-rich ores at Lisheen, Ireland - Max Frenzel; Markus Röhner; Nigel J. Cook; Sarah Gilbert; Cristiana L. Ciobanu; John F. Güven (Mineralium Deposita, 2025)
The Irish Orefield is characterised by the presence of both Zn-Pb- and Cu-Ni-As-rich deposits, prospects, and orebodies in similar structural and stratigraphic positions. However, the genetic relationships between these mineralisation types are still debated. In this article, we present new mineralogical, paragenetic, and mineral-chemical observations from the Cu-Ni-As-rich ores at the classic Lisheen deposit, County Tipperary. These observations indicate the intimate association and cogenetic nature of these ores with the more abundant Zn-Pb-rich mineralisation. Specifically, both mineralisation types appear to have formed at the same time, under similar physicochemical conditions, and from the same ore fluids. In addition, both types of mineralisation contain elevated Ge contents. The cogenetic nature of the two mineralisation types, the relative absence of Cu-Ni-As-rich ores from most of the larger Irish-type Zn-Pb deposits compared to expectations derived from probable ore fluid compositions, and finally, the known geological characteristics of larger Cu-Ni-As-rich ore bodies, like Gortdrum, indicate that significant Cu-Ni-As-rich mineralisation could be present at lower stratigraphic levels across the Irish Orefield. Areas with extensive known Zn-Pb mineralisation are expected to be particularly prospective for such ores, which may occur at stratigraphic levels as deep as the Old Red Sandstone. This may have additional implications beyond Ireland, and could point to the potential for undiscovered Cu-rich ores in low-temperature carbonate-hosted Zn-Pb districts elsewhere.

Length–Weight Relationships of the Prized Sea Cucumber Holothuria lessoni from In Situ and Ex Situ Measurements - Lea A. F. Djenidi; Steven W. Purcell; Aaron W. Thornton; Hugues Gossuin; Antoine Gilbert (Journal of Marine Science and Engineering, 2024)
Fisheries science draws on morphometric data for stock assessments. Length–weight relationships are essential for estimating body weight from length measurements taken either underwater (in situ) or out of the water (ex situ). We examined morphometric models for the high-valued sea cucumber, Holothuria lessoni. From 77 specimens captured in 2024 (mean weight ± SD: 1774 ± 372 g), we measured body length and width in situ and ex situ, then weighed the animals ex situ. We compared morphometric models using four biometric parameters. The fitted relationships were more statistically significant (p

Chemical profiling of organic contaminants in rural surface waters combining target and non-target LC-HRMS/MS analysis - Alfonso Fernández-García; Ana B. Martínez-Piernas; David Moreno-González; Bienvenida Gilbert-López; Juan F. García-Reyes (Science of The Total Environment, 2024)

The subreach effect: Multi-scale analysis reveals climate and irrigation infrastructure effects on flow intermittency in a regulated desert river - Eliza I. Gilbert; Thomas F. Turner; Melanie E. Moses; Alex J. Webster (Journal of Hydrology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Genome‐wide population affinities and signatures of adaptation in hydruntines, sussemiones and Asian wild asses - Jianfei Pan; Xuexue Liu; Mateusz Baca; Laure Calvière‐Tonasso; Stéphanie Schiavinato; Loreleï Chauvey; Gaétan Tressières; Aude Perdereau; Jean‐Marc Aury; Pedro H. Oliveira; Patrick Wincker; Aida Abdykanova; et al. (Molecular Ecology, 2024)
The extremely rich palaeontological record of the horse family, also known as equids, has provided many examples of macroevolutionary change over the last ~55 Mya. This family is also one of the most documented at the palaeogenomic level, with hundreds of ancient genomes sequenced. While these data have advanced understanding of the domestication history of horses and donkeys, the palaeogenomic record of other equids remains limited. In this study, we have generated genome‐wide data for 25 ancient equid specimens spanning over 44 Ky and spread across Anatolia, the Caucasus, Central Asia and Mongolia. Our dataset includes the genomes from two extinct species, the European wild ass, Equus hydruntinus , and the sussemione Equus ovodovi . We document, for the first time, the presence of sussemiones in Mongolia and their survival around ~3.9 Kya, a finding that should be considered when discussing the timing of the first arrival of the domestic horse in the region. We also identify strong spatial differentiation within the historical ecological range of Asian wild asses, Equus hemionus , and incomplete reproductive isolation in several groups yet considered as different species. Finally, we find common selection signatures at ANTXR2 gene in European, Asian and African wild asses. This locus, which encodes a receptor for bacterial toxins, shows no selection signal in E. ovodovi , but a 5.4‐kb deletion within intron 7. Whether such genetic modifications played any role in the sussemione extinction remains unknown.

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Microplastic and other anthropogenic microparticles in Arctic char (Salvelinus alpinus) and their coastal habitat: A first-look at a central Canadian Arctic commercial fishery - Bonnie M. Hamilton; Les N. Harris; Beverly Maksagak; Emilie Nero; Matthew J.H. Gilbert; Jennifer F. Provencher; Chelsea M. Rochman (Science of The Total Environment, 2024)

A multispecies hierarchical model to integrate count and distance‐sampling data - Neil A. Gilbert; Caroline M. Blommel; Matthew T. Farr; David S. Green; Kay E. Holekamp; Elise F. Zipkin (Ecology, 2024)
Integrated community models—an emerging framework in which multiple data sources for multiple species are analyzed simultaneously—offer opportunities to expand inferences beyond the single‐species and single‐data‐source approaches common in ecology. We developed a novel integrated community model that combines distance sampling and single‐visit count data; within the model, information is shared among data sources (via a joint likelihood) and species (via a random‐effects structure) to estimate abundance patterns across a community. Parameters relating to abundance are shared between data sources, and the model can specify either shared or separate observation processes for each data source. Simulations demonstrated that the model provided unbiased estimates of abundance and detection parameters even when detection probabilities varied between the data types. The integrated community model also provided more accurate and more precise parameter estimates than alternative single‐species and single‐data‐source models in many instances. We applied the model to a community of 11 herbivore species in the Masai Mara National Reserve, Kenya, and found considerable interspecific variation in response to local wildlife management practices: Five species showed higher abundances in a region with passive conservation enforcement (median across species: 4.5× higher), three species showed higher abundances in a region with active conservation enforcement (median: 3.9× higher), and the remaining three species showed no abundance differences between the two regions. Furthermore, the community average of abundance was slightly higher in the region with active conservation enforcement but not definitively so (posterior mean: higher by 0.20 animals; 95% credible interval: 1.43 fewer animals, 1.86 more animals). Our integrated community modeling framework has the potential to expand the scope of inference over space, time, and levels of biological organization, but practitioners should carefully evaluate whether model assumptions are met in their systems and whether data integration is valuable for their applications.

Occurrence and risk assessment of pesticides and their transformation products related to olive groves in surface waters of the Guadalquivir river basin - Alfonso Fernández-García; Ana B. Martínez-Piernas; David Moreno-González; Bienvenida Gilbert-López; Antonio Molina-Díaz; Juan F. García-Reyes (Chemosphere, 2024)

A century of statistical Ecology - Neil A. Gilbert; Bruna R. Amaral; Olivia M. Smith; Peter J. Williams; Sydney Ceyzyk; Samuel Ayebare; Kayla L. Davis; Wendy Leuenberger; Jeffrey W. Doser; Elise F. Zipkin (Ecology, 2024)
As data and computing power have surged in recent decades, statistical modeling has become an important tool for understanding ecological patterns and processes. Statistical modeling in ecology faces two major challenges. First, ecological data may not conform to traditional methods, and second, professional ecologists often do not receive extensive statistical training. In response to these challenges, the journal Ecology has published many innovative statistical ecology papers that introduced novel modeling methods and provided accessible guides to statistical best practices. In this paper, we reflect on Ecology 's history and its role in the emergence of the subdiscipline of statistical ecology, which we define as the study of ecological systems using mathematical equations, probability, and empirical data. We showcase 36 influential statistical ecology papers that have been published in Ecology over the last century and, in so doing, comment on the evolution of the field. As data and computing power continue to increase, we anticipate continued growth in statistical ecology to tackle complex analyses and an expanding role for Ecology to publish innovative and influential papers, advancing the discipline and guiding practicing ecologists.

Exposure to Nickel–Cadmium Contamination of Drinking Water Culminates in Liver Cirrhosis, Renal Azotemia, and Metabolic Stress in Rats - Augustine Apiamu; Oghenetega J. Avwioroko; Uduenevwo F. Evuen; Helen E. Kadiri; Enyohwo D. Kpomah; Akpovwehwee A. Anigboro; Gilbert Ugbebor; Samuel O. Asagba (Biological Trace Element Research, 2024)

Expert-driven play Fairway Analysis applied to the Azufral Volcano Geothermal Area in southwestern Colombia - Emmanuel Olvera-García; Bridget F. Ayling; Jesús B. Rueda-Gutiérrez; Anieri M. Morales Rivera; Gilbert F. Rodríguez-Rodríguez; Jaison Malo; Jefferson Sánchez; Yeimy Rodríguez-Molina; Yerson Pardo; Yenny P. Casallas-Veloza; J. Camilo Matiz-León; Gina Rodríguez-Ospina; et al. (Geothermics, 2023)

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Steven A. Murawski; Patrick T. Schwing; William F. Patterson; Tracey T. Sutton; Paul A. Montagna; Rosanna J. Milligan; Samantha B. Joye; Len Thomas; Joshua P. Kilborn; Claire B. Paris; Robin Faillettaz; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper provides an overview of a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “eco-types”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each eco-type were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all eco-types and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open-ocean and deep benthic eco-types has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.

Electrocardiogram to Determine Mitral and Aortic Valve Opening and Closure - M. Rifqi Aufan; Zachary T. Jost; Neal J. Miller; Oleg F. Sharifov; Himanshu Gupta; Gilbert J. Perry; J. Michael Wells; Thomas S. Denney; Steven G. Lloyd (Cardiovascular Engineering and Technology, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Effects of ants on riparian poplars: an ex situ experiment of biotic interaction - D. Corenblit; B. Corbara; R. Cereghino; A. Dejean; P. Duran; V. Garófano-Gómez; F. Gilbert; E. González-Sargas; F. Julien; L. Lambs; C. Mainguin; L. Mazal; et al. (Arthropod-Plant Interactions, 2023)

Mineralogical, magnetic and geochemical data constrain the pathways and extent of weathering of mineralized sedimentary rocks - Sergio Carrero; Sarah P. Slotznick; Sirine C. Fakra; M. Cole Sitar; Sharon E. Bone; Jeffrey L. Mauk; Andrew H. Manning; Nicholas L. Swanson-Hysell; Kenneth H Williams; Jillian F. Banfield; Benjamin Gilbert (Geochimica et Cosmochimica Acta, 2023)

Life-history omnivory in the fairy shrimp Branchinecta orientalis (Branchiopoda: Anostraca) - Dunja Lukić; Navid Pormehr; Lynda Beladjal; Csaba F. Vad; Robert Ptacnik; Gilbert Van Stappen; Naser Agh; Zsόfia Horváth (Hydrobiologia, 2023)
Very little is known about the feeding of naupliar and juvenile life stages of omnivorous fairy shrimps (Crustacea: Anostraca). Here, we aim to reveal whether the fairy shrimp Branchinecta orientalis is an ontogenetic omnivore and at which age and ontogenetic stage they gain the ability to feed on zooplankton. We assess how food uptake rates change with age until reaching maturity by providing algae (pico- and nanoplanktonic unicellular algae) and zooplankton (rotifers and copepod nauplii) as food in individual experiments. We found that the fairy shrimp B. orientalis started to feed on both types of algal prey immediately after hatching. Nanoplanktonic algae likely represented the most important food source until reaching maturity. Moreover, fairy shrimps started to feed on zooplankton already when they were 7 days old. Slow-moving rotifers gradually gained importance in the fairy shrimp diet with time. Our results reveal an ontogenetic change in the prey spectrum of fairy shrimp. The systematic shift towards omnivory likely affects both phyto- and zooplankton community composition, possibly contributing to temporal changes in food web dynamics in fairy shrimp habitats, and temporary ponds, which may warrant more detailed investigations in future studies.

How does co-produced research influence adaptive capacity? Lessons from a cross-case comparison - Sarah P. Church; Chloe B. Wardropper; Emily Usher; Liam F. Bean; Ashlie Gilbert; Francis R. Eanes; Jessica D. Ulrich-Schad; Nicholas Babin; Pranay Ranjan; Jackie M. Getson; Laura A. Esman; Linda S. Prokopy (Socio-Ecological Practice Research, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The dilemma of Guinea grass (Megathyrsus maximus): a valued pasture grass and a highly invasive species - Aaron C. Rhodes; Robert M. Plowes; John A. Goolsby; John F. Gaskin; Boaz Musyoka; Paul-André Calatayud; Massimo Cristofaro; Eric D. Grahmann; Dino J. Martins; Lawrence E. Gilbert (Biological Invasions, 2021)

Hilfsmittel und Verfahren für zellbasiertes high content imaging - Daniel F. Gilbert; Oliver Friedrich; Christian Lesko; Kristin Hartmann (BIOspektrum, 2021)
Cell-based high content imaging has become a versatile and powerful method for studying e. g. cellular viability, morphology or physiology. However, high content imaging and its various applications require complex as well as expensive hardware and consumables, limiting its utility and usability. To broaden the applicability of cell-based high content imaging, we have developed tools and assaying techniques being exemplary portrayed in this article.

Species niches, not traits, determine abundance and occupancy patterns: A multi‐site synthesis - Nicholas A. C. Marino; Régis Céréghino; Benjamin Gilbert; Jana S. Petermann; Diane S. Srivastava; Paula M. de Omena; Fabiola Ospina Bautista; Laura Melissa Guzman; Gustavo Q. Romero; M. Kurtis Trzcinski; Ignacio M. Barberis; Bruno Corbara; et al. (Global Ecology and Biogeography, 2020)
Aim Locally abundant species are usually widespread, and this pattern has been related to properties of the niches and traits of species. However, such explanations fail to account for the potential of traits to determine species niches and often overlook statistical artefacts. Here, we examine how trait distinctiveness determines the abilities of species to exploit either common habitats (niche position) or a range of habitats (niche breadth) and how niche position and breadth, in turn, affect abundance and occupancy. We also examine how statistical artefacts moderate these relationships. Location Sixteen sites in the Neotropics. Time period 1993–2014. Major taxa studied Aquatic invertebrates from tank bromeliads. Methods We measured the environmental niche position and breadth of each species and calculated its trait distinctiveness as the average trait difference from all other species at each site. Then, we used a combination of structural equation models and a meta‐analytical approach to test trait–niche relationships and a null model to control for statistical artefacts. Results The trait distinctiveness of each species was unrelated to its niche properties, abundance and occupancy. In contrast, niche position was the main predictor of abundance and occupancy; species that used the most common environmental conditions found across bromeliads were locally abundant and widespread. Contributions of niche breadth to such patterns were attributable to statistical artefacts, indicating that effects of niche breadth might have been overestimated in previous studies. Main conclusions Our study reveals the generality of niche position in explaining one of the most common ecological patterns. The robustness of this result is underscored by the geographical extent of our study and our control of statistical artefacts. We call for a similar examination across other systems, which is an essential task to understand the drivers of commonness across the tree of life.

Implications of different nitrogen input sources for potential production and carbon flux estimates in the coastal Gulf of Mexico (GOM) and Korean Peninsula coastal waters - Jongsun Kim; Piers Chapman; Gilbert Rowe; Steven F. DiMarco; Daniel C. O. Thornton (Ocean Science, 2020)
The coastal Gulf of Mexico (GOM) and coastal sea off the Korean Peninsula (CSK) both suffer from human-induced eutrophication. We used a nitrogen (N) mass balance model in two different regions with different nitrogen input sources to estimate organic carbon fluxes and predict future carbon fluxes under different model scenarios. The coastal GOM receives nitrogen predominantly from the Mississippi and Atchafalaya rivers and atmospheric nitrogen deposition is only a minor component in this region. In the CSK, groundwater and atmospheric nitrogen deposition are more important controlling factors. Our model includes the fluxes of nitrogen to the ocean from the atmosphere, groundwater and rivers, based on observational and literature data, and identifies three zones (brown, green and blue waters) in the coastal GOM and CSK with different productivity and carbon fluxes. Based on our model results, the potential primary production rate in the inner (brown water) zone are over 2 gC m−2 d−1 (GOM) and 1.5 gC m−2 d−1 (CSK). In the middle (green water) zone, potential production is from 0.1 to 2 (GOM) and 0.3 to 1.5 gC m−2 d−1 (CSK). In the offshore (blue water) zone, productivity is less than 0.1 (GOM) and 0.3 (CSK) gC m−2 d−1. Through our model scenario results, overall oxygen demand in the GOM will increase approximately 21 % if we fail to reduce riverine N input, likely increasing considerably the area affected by hypoxia. Comparing the results from the USA with those from the Korean Peninsula shows the importance of considering both riverine and atmospheric inputs of nitrogen. This has direct implications for investigating how changes in energy technologies can lead to changes in the production of various atmospheric contaminants that affect air quality, climate and the health of local populations.

A Novel Method of Using Iron Nanoparticles from Coal Fly Ash or Ferric Chloride for Acid Mine Drainage Remediation - Crisanda Gilbert; Olushola S. Ayanda; Olanrewaju O. Fatoba; Godfrey Madzivire; Leslie F. Petrik (Mine Water and the Environment, 2019)

Predation drives recurrent convergence of an interspecies mutualism - William E. Feeney; Rohan M. Brooker; Lane N. Johnston; James D. J. Gilbert; Marc Besson; David Lecchini; Danielle L. Dixson; Peter F. Cowman; Andrea Manica (Ecology Letters, 2019)
Mutualisms are important ecological interactions that underpin much of the world's biodiversity. Predation risk has been shown to regulate mutualism dynamics in species‐specific case studies; however, we lack studies which investigate whether predation can also explain broader patterns of mutualism evolution. We report that fish‐anemone mutualisms have evolved on at least 55 occasions across 16 fish families over the past 60 million years and that adult body size is associated with the ontogenetic stage of anemone mutualisms: larger‐bodied species partner with anemones as juveniles, while smaller‐bodied species partner with anemones throughout their lives. Field and laboratory studies show that predators target smaller prey, that smaller fishes associate more with anemones, and that these relationships confer protection to small fishes. Our results indicate that predation is likely driving the recurrent convergent evolution of fish‐anemone mutualisms and suggest that similar ecological processes may have selected convergence in interspecies interactions in other animal clades.

Obituary: Siv Aina Jensen Leendertz (Born Siv Aina Jensen: 1973–2018) - Chantal Akoua-Koffi; Sandra Beermann; Sébastien Calvignac-Spencer; Emmanuel Couacy-Hymann; Helene De Nys; Bernhard Ehlers; Thomas Gillespie; Jeffrey Gilbert; Jan F. Gogarten; Sandra J. Laney; Felix Lankester; Fabian H. Leendertz; et al. (International Journal of Primatology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Conservation implications of physiological carry‐over effects in bats recovering from white‐nose syndrome - Christina M. Davy; Gabriela F. Mastromonaco; Julia L. Riley; James H. Baxter‐Gilbert; Heather Mayberry; Craig K.R. Willis (Conservation Biology, 2017)
Although it is well documented that infectious diseases can pose threats to biodiversity, the potential long‐term consequences of pathogen exposure on individual fitness and its effects on population viability have rarely been studied. We tested the hypothesis that pathogen exposure causes physiological carry‐over effects with a pathogen that is uniquely suited to this question because the infection period is specific and time limited. The fungus Pseudogymnoascus destructans causes white‐nose syndrome (WNS) in hibernating bats, which either die due to the infection while hibernating or recover following emergence from hibernation. The fungus infects all exposed individuals in an overwintering site simultaneously, and bats that survive infection during hibernation clear the pathogen within a few weeks following emergence. We quantified chronic stress during the active season, when bats are not infected, by measuring cortisol in bat claws. Free‐ranging Myotis lucifugus who survived previous exposure to P. destructans had significantly higher levels of claw cortisol than naïve individuals. Thus, cryptic physiological carry‐over effects of pathogen exposure may persist in asymptomatic, recovered individuals. If these effects result in reduced survival or reproductive success, they could also affect population viability and even act as a third stream in the extinction vortex. For example, significant increases in chronic stress, such as those indicated here, are correlated with reduced reproductive success in a number of species. Future research should directly explore the link between pathogen exposure and the viability of apparently recovered populations to improve understanding of the true impacts of infectious diseases on threatened populations.

Maßgeschneiderte Methoden und Technologien für high content imaging - Daniel F. Gilbert (BIOspektrum, 2017)

Leeches as a source of mammalian viral DNA and RNA—a study in medicinal leeches - Marie-Louise Kampmann; Ida Bærholm Schnell; Randi Holm Jensen; Jan Axtner; Adam F. Sander; Anders J. Hansen; Mads F. Bertelsen; Alex D. Greenwood; M. Thomas P. Gilbert; Andreas Wilting (European Journal of Wildlife Research, 2017)

Hong Kong’s rich marine biodiversity: the unseen wealth of South China’s megalopolis - Terence P. T. Ng; Martin C. F. Cheng; Kevin K. Y. Ho; Gilbert C. S. Lui; Kenneth M. Y. Leung; Gray A. Williams (Biodiversity and Conservation, 2017)

Bioactivity evaluation of cudraxanthone I, neocyclomorusin and (9βh)-3β-acetoxylanosta-7,24-diene isolated from Milicia excelsa Welw. C. C. Berg (Moraceae) - Feyza Oke-Altuntas; Gilbert D.W. F. Kapche; Judith L. Nantchouang Ouete; Ibrahim Demirtas; Merve B. Koc; Bonaventure T. Ngadjui (Medicinal Chemistry Research, 2016)

Assessment of sulfide production risk in soil during the infiltration of domestic wastewater treated by a sulfur-utilizing denitrification process - L. Ghorbel; L. Coudert; Y. Gilbert; G. Mercier; J. F. Blais (Environmental Science and Pollution Research, 2016)

A poor international standard for trap selectivity threatens carnivore conservation - Emilio Virgós; Jorge Lozano; Sara Cabezas-Díaz; David W. Macdonald; Andrzej Zalewski; Juan Carlos Atienza; Gilbert Proulx; William J. Ripple; Luis M. Rosalino; Margarida Santos-Reis; Paul J. Johnson; Aurelio F. Malo; et al. (Biodiversity and Conservation, 2016)

Measuring kinetic drivers of pneumolysin pore structure - Robert J. C. Gilbert; Andreas F.-P. Sonnen (European Biophysics Journal, 2016)

Ecological Developmental Biology: Interpreting Developmental Signs - Scott F. Gilbert (Biosemiotics, 2016)

Overview and modeling of mechanical and thermomechanical impact of underground coal gasification exploitation - F. Laouafa; R. Farret; S. Vidal-Gilbert; J-B. Kazmierczak (Mitigation and Adaptation Strategies for Global Change, 2016)

Seed-Specific Stable Expression of the α-AI1 Inhibitor in Coffee Grains and the In Vivo Implications for the Development of the Coffee Berry Borer - Érika V. S. Albuquerque; Caroline A. Bezerra; Juan V. Romero; Jorge W. A. Valencia; Arnubio Valencia-Jiménez; Lucas M. Pimenta; Aulus E. A. D. Barbosa; Maria C. M. Silva; Ana M. Meneguim; Maria Eugênia L. Sá; Gilbert Engler; Janice de Almeida-Engler; et al. (Tropical Plant Biology, 2015)

The Birth of the Holobiont: Multi-species Birthing Through Mutual Scaffolding and Niche Construction - Lynn Chiu; Scott F. Gilbert (Biosemiotics, 2015)

An example of enhanced tephra deposition driven by topographically induced atmospheric turbulence - Sebastian F. L. Watt; Jennie S. Gilbert; Arnau Folch; Jeremy C. Phillips; Xiaoming M. Cai (Bulletin of Volcanology, 2015)

Severity markers in severe leptospirosis: a cohort study - M. Mikulski; P. Boisier; F. Lacassin; M.-E. Soupé-Gilbert; C. Mauron; L. Bruyere-Ostells; D. Bonte; Y. Barguil; A.-C. Gourinat; M. Matsui; F. Vernel-Pauillac; C. Goarant (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Corrigendum - Paula F. Campos; Michael Hofreiter; Ludovic Orlando; Eske Willerslev; M. Thomas P. Gilbert (Molecular Ecology, 2014)

Symbiosis as the way of eukaryotic life: The dependent co-origination of the body - Scott F Gilbert (Journal of Biosciences, 2014)

Are HPV vaccination services accessible to high-risk communities? A spatial analysis of HPV-associated cancer and Chlamydia rates and safety-net clinics - Jennifer Tsui; Hector P. Rodriguez; Gilbert C. Gee; Loraine A. Escobedo; Gerald F. Kominski; Roshan Bastani (Cancer Causes & Control, 2013)

Biomass Production and Composition of Perennial Grasses Grown for Bioenergy in a Subtropical Climate Across Florida, USA - Jeffrey R. Fedenko; John E. Erickson; Kenneth R. Woodard; Lynn E. Sollenberger; Joao M. B. Vendramini; Robert. A. Gilbert; Zane R. Helsel; Gary F. Peter (BioEnergy Research, 2013)

DNA from soil mirrors plant taxonomic and growth form diversity - N. G. YOCCOZ; K. A. BRÅTHEN; L. GIELLY; J. HAILE; M. E. EDWARDS; T. GOSLAR; H. Von STEDINGK; A. K. BRYSTING; E. COISSAC; F. POMPANON; J. H. SØNSTEBØ; C. MIQUEL; et al. (Molecular Ecology, 2012)
Ecosystems across the globe are threatened by climate change and human activities. New rapid survey approaches for monitoring biodiversity would greatly advance assessment and understanding of these threats. Taking advantage of next‐generation DNA sequencing, we tested an approach we call metabarcoding: high‐throughput and simultaneous taxa identification based on a very short (usually

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Natural outbreak of Streptococcus agalactiae (GBS) infection in wild giant Queensland grouper, Epinephelus lanceolatus (Bloch), and other wild fish in northern Queensland, Australia - R O Bowater; J Forbes‐Faulkner; I G Anderson; K Condon; B Robinson; F Kong; G L Gilbert; A Reynolds; S Hyland; G McPherson; J O’ Brien; D Blyde (Journal of Fish Diseases, 2012)
Ninety‐three giant Queensland grouper, Epinephelus lanceolatus (Bloch), were found dead in Queensland, Australia, from 2007 to 2011. Most dead fish occurred in northern Queensland, with a peak of mortalities in Cairns in June 2008. In 2009, sick wild fish including giant sea catfish, Arius thalassinus (Rüppell), and javelin grunter, Pomadasys kaakan (Cuvier), also occurred in Cairns. In 2009 and 2010, two disease epizootics involving wild stingrays occurred at Sea World marine aquarium. Necropsy, histopathology, bacteriology and PCR determined that the cause of deaths of 12 giant Queensland grouper, three wild fish, six estuary rays, Dasyatis fluviorum (Ogilby), one mangrove whipray, Himantura granulata (Macleay), and one eastern shovelnose ray, Aptychotrema rostrata (Shaw), was Streptococcus agalactiae septicaemia. Biochemical testing of 34 S. agalactiae isolates from giant Queensland grouper, wild fish and stingrays showed all had identical biochemical profiles. The 16S rRNA gene sequences of isolates confirmed all isolates were S. agalactiae ; genotyping of selected S. agalactiae isolates showed the isolates from giant Queensland grouper were serotype Ib, whereas isolates from wild fish and stingrays closely resembled serotype II. This is the first report of S. agalactiae from wild giant Queensland grouper and other wild tropical fish and stingray species in Queensland, Australia.

Variation in wind and piscivorous predator fields affecting the survival of Atlantic salmon, Salmo salar , in the Gulf of Maine - K. D. FRIEDLAND; J. P. MANNING; J. S. LINK; J. R. GILBERT; A. T. GILBERT; A. F. O’CONNELL (Fisheries Management and Ecology, 2012)
Observations relevant to the North American stock complex of Atlantic salmon, Salmo salar L., suggest that marine mortality is influenced by variation in predation pressure affecting post‐smolts during the first months at sea. This hypothesis was tested for Gulf of Maine (GOM) stocks by examining wind pseudostress and the distribution of piscivorous predator fields potentially affecting post‐smolts. Marine survival has declined over recent decades with a change in the direction of spring winds, which is likely extending the migration of post‐smolts by favouring routes using the western GOM. In addition to changes in spring wind patterns, higher spring sea surface temperatures have been associated with shifting distributions of a range of fish species. The abundance of several pelagic piscivores, which based on their feeding habits may predate on salmon post‐smolts, has increased in the areas that serve as migration corridors for post‐smolts. In particular, populations of silver hake, Merluccius bilinearis (Mitchell), red hake, Urophycis chuss (Walbaum), and spiny dogfish, Squalus acanthias L., increased in size in the portion of the GOM used by post‐smolts. Climate variation and shifting predator distributions in the GOM are consistent with the predator hypothesis of recruitment control suggested for the stock complex.

Erratum to: Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

In vitro hepatoprotective and antioxidant activities of crude extract and isolated compounds from Ficus gnaphalocarpa - Donfack J. Hubert; Amadou Dawe; Ngueguim T. Florence; Kapche D. W. F. Gilbert; Tchana N. Angele; D. Buonocore; P. Vita Finzi; G. Vidari; Ngadjui T. Bonaventure; Fulvio Marzatico; Moundipa F. Paul (Inflammopharmacology, 2011)

Ancient DNA sequences point to a large loss of mitochondrial genetic diversity in the saiga antelope ( Saiga tatarica ) since the Pleistocene - PAULA F. CAMPOS; TOMMY KRISTENSEN; LUDOVIC ORLANDO; ANDREI SHER; MARINA V. KHOLODOVA; ANDERS GÖTHERSTRÖM; MICHAEL HOFREITER; DOROTHÉE G. DRUCKER; PAVEL KOSINTSEV; ALEXEI TIKHONOV; GENNADY. F. BARYSHNIKOV; ESKE WILLERSLEV; et al. (Molecular Ecology, 2010)
Prior to the Holocene, the range of the saiga antelope ( Saiga tatarica ) spanned from France to the Northwest Territories of Canada. Although its distribution subsequently contracted to the steppes of Central Asia, historical records indicate that it remained extremely abundant until the end of the Soviet Union, after which its populations were reduced by over 95%. We have analysed the mitochondrial control region sequence variation of 27 ancient and 38 modern specimens, to assay how the species’ genetic diversity has changed since the Pleistocene. Phylogenetic analyses reveal the existence of two well‐supported, and clearly distinct, clades of saiga. The first, spanning a time range from >49 500 14 C ybp to the present, comprises all the modern specimens and ancient samples from the Northern Urals, Middle Urals and Northeast Yakutia. The second clade is exclusive to the Northern Urals and includes samples dating from between 40 400 to 10 250 14 C ybp. Current genetic diversity is much lower than that present during the Pleistocene, an observation that data modelling using serial coalescent indicates cannot be explained by genetic drift in a population of constant size. Approximate Bayesian Computation analyses show the observed data is more compatible with a drastic population size reduction ( c. 66–77%) following either a demographic bottleneck in the course of the Holocene or late Pleistocene, or a geographic fragmentation (followed by local extinction of one subpopulation) at the Holocene/Pleistocene transition.

Accumulation Capacities of Particulate Matter in an Acrocarpous and a Pleurocarpous Moss Exposed at Three Differently Polluted Sites (Industrial, Urban and Rural) - J. Fabure; C. Meyer; F. Denayer; A. Gaudry; D. Gilbert; N. Bernard (Water, Air, & Soil Pollution, 2010)

Distribution patterns of wintering sea ducks in relation to the North Atlantic Oscillation and local environmental characteristics - Elise F. Zipkin; Beth Gardner; Andrew T. Gilbert; Allan F. O’Connell; J. Andrew Royle; Emily D. Silverman (Oecologia, 2010)

A multidisciplinary study of archaeological grape seeds - Enrico Cappellini; M. Thomas P. Gilbert; Filippo Geuna; Girolamo Fiorentino; Allan Hall; Jane Thomas-Oates; Peter D. Ashton; David A. Ashford; Paul Arthur; Paula F. Campos; Johan Kool; Eske Willerslev; et al. (The Science of Nature, 2010)

Variants in toll-like receptors 2 and 9 influence susceptibility to pulmonary tuberculosis in Caucasians, African-Americans, and West Africans - Digna Rosa Velez; Christian Wejse; Martin E. Stryjewski; Eduardo Abbate; William F. Hulme; Jamie L. Myers; Rosa Estevan; Sara G. Patillo; Rikke Olesen; Alessandra Tacconelli; Giorgio Sirugo; John R. Gilbert; et al. (Human Genetics, 2010)

NOS2A, TLR4, and IFNGR1 interactions influence pulmonary tuberculosis susceptibility in African-Americans - Digna Rosa Velez; William F. Hulme; Jamie L. Myers; J. Brice Weinberg; Marc C. Levesque; Martin E. Stryjewski; Eduardo Abbate; Rosa Estevan; Sara G. Patillo; John R. Gilbert; Carol D. Hamilton; William K. Scott (Human Genetics, 2009)

Aerobic respiration and hypoxia in the Lower St. Lawrence Estuary: Stable isotope ratios of dissolved oxygen constrain oxygen sink partitioning - Moritz F. Lehmann; Bruce Barnett; Y. Gélinas; Denis Gilbert; Roxane J. Maranger; Alfonso Mucci; Bjorn Sundby; Benoit Thibodeau (Limnology and Oceanography, 2009)
We measured the concentration and the stable isotope ratios of dissolved oxygen in the water column in the Estuary and Gulf of St. Lawrence to determine the relative importance of pelagic and benthic dissolved oxygen respiration to the development of hypoxic deep waters. The progressive landward decrease of dissolved oxygen in the bottom waters along the axis of the Laurentian Channel (LC) is accompanied by an increase in the 18 O: 16 O ratio, as would be expected from O‐isotope fractionation associated with bacterial oxygen respiration. The apparent O‐isotope effect, ε O‐app , of 10.8% reveals that community O‐isotope fractionation is significantly smaller than if bacterial respiration occurred solely in the water column. Our observation can best be explained by a contribution of benthic O 2 consumption occurring with a strongly reduced O‐isotope effect at the scale of sediment‐water exchange (ε O‐sed ~ 7%). The value for ε O‐sed was estimated from benthic O 2 exchange simulations using a one‐dimensional diffusion‐reaction O‐isotope model. Adopting this ε O‐sed value, and given the observed community O‐isotope fractionation, we calculate that approximately two thirds of the ecosystem respiration occurs within the sediment, in reasonable agreement with direct respiration measurements. Based on the difference between dissolved oxygen concentrations in the deep waters of the Lower St. Lawrence Estuary and in the water that enters the LC at Cabot Strait, we estimate an average respiration rate of 5500 mmol O 2 m −2 yr −1 for the 100‐m‐thick layer of bottom water along the LC, 3540 mmol O 2 m −2 yr −1 of which is attributed to bacterial benthic respiration.

Ageing and cancer as diseases of epigenesis - Scott F. Gilbert (Journal of Biosciences, 2009)

Effects of nicotine on novelty detection and memory recognition performance: double-blind, placebo-controlled studies of smokers and nonsmokers - Brett Froeliger; David G. Gilbert; F. Joseph McClernon (Psychopharmacology, 2009)

Can Campylobacter coli induce Guillain-Barré syndrome? - A. van Belkum; B. Jacobs; E. van Beek; R. Louwen; W. van Rijs; L. Debruyne; M. Gilbert; J. Li; A. Jansz; F. Mégraud; H. Endtz (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

American precursors of evo-devo: ecology, cell lineage, and pastimes unworthy of the Deity - Scott F. Gilbert (Theory in Biosciences, 2008)

A systemic approach for the development of FHB resistant germplasm accelerates genetic progress - A. Comeau; F. Langevin; V. Caetano; S. Haber; M. Savard; H. Voldeng; G. Fedak; Y. Dion; S. Rioux; J. Gilbert; D. Somers; R. Martin (Cereal Research Communications, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

The national roots of evo–devo - S. F. Gilbert; G. S. Levit (Theory in Biosciences, 2007)

Chromosomal evolution in tenrecs (Microgale and Oryzorictes, Tenrecidae) from the Central Highlands of Madagascar - C. Gilbert; S. M. Goodman; V. Soarimalala; L. E. Olson; P. C. M. O’Brien; F. F. B. Elder; F. Yang; M. A. Ferguson-Smith; T. J. Robinson (Chromosome Research, 2007)

Promiscuous, non-catalytic, tandem carbohydrate-binding modules modulate the cell-wall structure and development of transgenic tobacco (Nicotiana tabacum) plants - Olawole O. Obembe; Evert Jacobsen; Jaap Timmers; Harry Gilbert; Anthony W. Blake; J. Paul Knox; Richard G. F. Visser; Jean-Paul Vincken (Journal of Plant Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Remnants of ancient genetic diversity preserved within captive groups of scimitar‐horned oryx ( Oryx dammah ) - A. IYENGAR; T. GILBERT; T. WOODFINE; J. M. KNOWLES; F. M. DINIZ; R. A. BRENNEMAN; E. E. LOUIS; N. MACLEAN (Molecular Ecology, 2007)
Scimitar‐horned oryx, now considered extinct in the wild, persists in large numbers in captivity. In this first molecular genetic study on this species, we explore the patterns of genetic diversity across European, North American, and a few other captive groups using microsatellite markers and mitochondrial control region sequencing. Strong population structure was not evident from microsatellite data but we discovered deep divergence within the mitochondrial DNA haplotypes from a network analysis where three disconnected networks were obtained, with estimated divergence times of c. 2.1–2.7 million years. Mismatch distribution analyses suggest population expansions c. 1.2 and 0.5 million years ago. We discuss our findings in the context of historical climatic changes in North Africa and use information obtained on current patterns of genetic diversity within captive groups to make recommendations for future captive management and reintroduction strategies.

Chromosome painting and molecular dating indicate a low rate of chromosomal evolution in golden moles (Mammalia, Chrysochloridae) - C. Gilbert; P. C. O’Brien; G. Bronner; F. Yang; A. Hassanin; M. A. Ferguson-Smith; T. J. Robinson (Chromosome Research, 2006)

Biotic interactions and plant invasions - Charles E. Mitchell; Anurag A. Agrawal; James D. Bever; Gregory S. Gilbert; Ruth A. Hufbauer; John N. Klironomos; John L. Maron; William F. Morris; Ingrid M. Parker; Alison G. Power; Eric W. Seabloom; Mark E. Torchin; et al. (Ecology Letters, 2006)
Introduced plant populations lose interactions with enemies, mutualists and competitors from their native ranges, and gain interactions with new species, under new abiotic conditions. From a biogeographical perspective, differences in the assemblage of interacting species, as well as in abiotic conditions, may explain the demographic success of the introduced plant populations relative to conspecifics in their native range. Within invaded communities, the new interactions and conditions experienced by the invader may influence both its demographic success and its effects on native biodiversity. Here, we examine indirect effects involving enemies, mutualists and competitors of introduced plants, and effects of abiotic conditions on biotic interactions. We then synthesize ideas building on Darwin's idea that the kinds of new interactions gained by an introduced population will depend on its relatedness to native populations. This yields a heuristic framework to explain how biotic interactions and abiotic conditions influence invader success. We conclude that species introductions generally alter plants’ interactions with enemies, mutualists and competitors, and that there is increasing evidence that these altered interactions jointly influence the success of introduced populations.

Education in sustainable production in US universities - Gilbert L. Rochon; Loring F. Nies; Chad T. Jafvert; Julie A. Stuart; Rabi H. Mohtar; Joseph Quansah; Akilah Martin (Clean Technologies and Environmental Policy, 2006)

Strategic approach to mitigating weather induced defects of wheat quality - F. R. Clarke; J. M. Clarke; R. M. DePauw; M. R. Fernandez; S. Fox; J. Gilbert; G. Humphreys; R. E. Knox; T. N. McCaig; D. Procunier; M. Sissons; D. Somers (Euphytica, 2005)

Foreword - Gilbert F. White (Mitigation and Adaptation Strategies for Global Change, 2005)

Mechanisms for the environmental regulation of gene expression: Ecological aspects of animal development - Scott F. Gilbert (Journal of Biosciences, 2005)

Foreword - Vidyanand Nanjundiah; Stuart A. Newman; Scott F. Gilbert (Journal of Biosciences, 2005)

Contribution of Natural History Collection Data to Biodiversity Assessment in National Parks - ALLAN F. O'CONNELL; ANDREW T. GILBERT; JEFF S. HATFIELD (Conservation Biology, 2004)
There has been mounting interest in the use of museum and herbaria collections to assess biodiversity; information is often difficult to locate and access, however, and few recommendations are available for effectively using natural history collections. As part of an effort to inventory vertebrates and vascular plants in U.S. national parks, we searched manually and by computer for specimens originating within or adjacent to 14 parks throughout the northeastern United States. We compared the number of specimens located to collection size to determine whether there was any effect on detection rate of specimens. We evaluated the importance of park characteristics (e.g., age since establishment, size, theme [natural vs. cultural]) for influencing the number of specimens found in a collection. We located >31,000 specimens and compiled associated records (hereafter referred to as specimens) from 78 collections; >9000 specimens were park‐significant, originating either within park boundaries or in the local township where the park was located. We found >2000 specimens by means of manual searches, which cost $0.001–0.15 per specimen searched and $0.81–151.95 per specimen found. Collection effort appeared relatively uniform between 1890 and 1980, with low periods corresponding to significant sociopolitical events. Detection rates for specimens were inversely related to collection size. Although specimens were most often located in collections within the region of interest, specimens can be found anywhere, particularly in large collections international in scope, suggesting that global searches will be necessary to evaluate historical biodiversity. Park characteristics indicated that more collecting effort occurred within or adjacent to larger parks established for natural resources than in smaller historical sites. Because many institutions have not yet established electronic databases for collections, manual searches can be useful for retrieving specimens. Our results show that thorough, systematic searching of natural history collections for park‐significant specimens can provide a historical perspective on biodiversity for park managers.

Acclimation of white lupin to phosphorus deficiency involves enhanced expression of genes related to organic acid metabolism - Claudia Uhde-Stone; Glena Gilbert; Jane M-F Johnson; Ralph Litjens; Kelly E. Zinn; Stephen J. Temple; Carroll P. Vance; Deborah L. Allan (Plant and Soil, 2003)

Stephen J Gould - Scott F. Gilbert (Journal of Biosciences, 2002)

New vistas for developmental biology - Scott F. Gilbert; Rocky S. Tuan (Journal of Biosciences, 2001)

A dual approach in the study of poly (ADP-ribose) polymerase: In vitro random mutagenesis and generation of deficient mice - Carlotta Trucco; Véronique Rolli; F. Javier Oliver; Eric Flatter; Murielle Masson; Françoise Dantzer; Claude Neidergang; Bernard Dutrillaux; Josiane Ménissier-de murcia; Gilbert de Murcia (Molecular and Cellular Biochemistry, 1999)

Conceptual breakthroughs in developmental biology - Scott F. Gilbert (Journal of Biosciences, 1998)

Expression and chromosomal localization of the Requiem gene - Theodore G. Gabig; Colin D. Crean; Alison Klenk; Haiyan Long; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Danielle Quincey; Fabienne Parente; Françoise Lespinasse; Georges F. Carle; Patrick Gaudray; et al. (Mammalian Genome, 1998)

Mutational analysis of the GDNF/RET-GDNFRα signaling complex in a kindred with vesicoureteral reflux - Sarah E. Shefelbine; Sangeeta Khorana; Pamela N. Schultz; Eileen Huang; Nicole Thobe; Zheng J. Hu; Gary M. Fox; Shuqian Jing; Gilbert J. Cote; R. F. Gagel (Human Genetics, 1998)

Effects of pentachlorophenol and other chemical preservatives on the health of wood-treating workers in Hawaii - F. I. Gilbert; C. E. Minn; R. C. Duncan; John Wilkinson (Archives of Environmental Contamination and Toxicology, 1990)

Genetic effects of chlorinated anilines and azobenzenes onSalmonella typhimurium - P. Gilbert; G. Saint-Ruf; F. Poncelet; M. Mercier (Archives of Environmental Contamination and Toxicology, 1980)

Nutritional and toxicological studies with growing pigs fed aquatic plant rations - Tuan N. Yap; Wilson G. Pond; Jung F. Wu; Gilbert S. Stoewsand; Patricia C. Wszolek; Donald J. Lisk (Archives of Environmental Contamination and Toxicology, 1979)

A pharmacokinetic model for predicting pesticide residues in fish - Stephen F. Krzeminski; Joseph T. Gilbert; John A. Ritts (Archives of Environmental Contamination and Toxicology, 1977)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

Crop and market news - B. A. Brown; H. C. Moore; P. N. Davis; J. F. Sharples; H. O. Werner; O. C. Hicks; J. Gilbert Borton; H. C. Odell; E. V. Hardenburg (American Journal of Potato Research, 1926)

Potato notes - C. Tice; H. G. Zuckerman; W. C. Edmundson; W. L. Floyd; G. W. Waller; A. J. Johnston; E. P. Miller; E. A. Stokdyk; G. L. Tiebout; H. C. Moore; Walter M. Peacock; Andrew Schnetzler; et al. (American Journal of Potato Research, 1925)

Seed potato certification notes - F. H. Harrington; J. Tucker; Alfred H. Gilbert (American Journal of Potato Research, 1924)

Potato notes - C. W. Tice; J. T. Rosa; A. E. Wilkinson; E. A. Stokdyk; E. L. Newdick; Verdal T. Maxwell; C. F. Clark; W. Stuart; Charles A. Thompson; J. Gilbert Borton; Ellwood Douglass; Orley G. Bowen; et al. (American Journal of Potato Research, 1924)

Potato notes - J. T. Rosa; E. A. Stokdyk; H. J. Wheeler; J. F. Hockey; H. O. Werner; W. H. Martin; O. G. Bowen; J. Gilbert Barton; Wm. B. Duryee; J. C. Crissey; A. H. C. Odell; C. R. Inglee; et al. (American Journal of Potato Research, 1924)

Certified seed potato notes - J. F. Hockey; E. V. Hardenburg; A. H. Gilbert (American Journal of Potato Research, 1924)

Seed certification notes - M. F. Barrus; W. Stuart; A. W. Tompkins; A. H. Gilbert; J. G. Milward (American Journal of Potato Research, 1924)